Message - Singh, Dr. (Mrs.) Anita (Universal Journal of Pharmaceutical Research, 2017)
Research thrives on collaboration and relies on efficient and effective exchange between those researching and developing new innovations – as well as with those that would use them. Incorporating this idea UJPR has been conceptualized to identify and extract best scientific research which can be integrated in existing and future collaborations in the field of life sciences. UJPR being a bimonthly journal with six issues being published in a year provides more opportunities and exposure in scientific world inviting high-performance papers with quantitative performance assessment by its renowned Editorial Board with excellent academic background and expertise ensuring high standards for publication for novel research. Over the upcoming issues, we plan to commence several new initiatives to make the journal more indulging and useful to our readers with main focus on publishing highest quality research with a particular importance on quality, safety, systems, and outcomes of research. This journal helps to develop an effective understanding in order to impart productivity and competence in life sciences by determining the challenges and probable approaches for overcoming them. I would like to congratulate and highly acknowledge the contribution made by the dedicated team of Editorial Board for their hard work towards making the journal truly influential publication. To conclude, I would thank the contributors and readers for their interest in the journal and encourage nurturing and intellectual minds for the next upcoming issue. Hope that the journal will continue to be a stimulating and knowledgeable resource for many years to come.